Both caffeine and Capsicum annuum fruit powder lower blood glucose levels and increase brown adipose tissue temperature in healthy adult males - Van Schaik, Lachlan; Kettle, Christine; Green, Rod; Wundersitz, Daniel; Gordon, Brett; Irving, Helen R.; Rathner, Joseph A. (Frontiers in Physiology, 2022)
Using a combination of respiratory gas exchange, infrared thermography, and blood glucose (BGL) analysis, we have investigated the impact of Capsicum annuum (C. annuum) fruit powder (475 mg) or caffeine (100 mg) on metabolic activity in a placebo controlled (lactose, 100 mg) double-blinded three-way cross-over-design experiment. Metabolic measurements were made on day 1 and day 7 of supplementation in eight adult male participants (22.2 ± 2 years of age, BMI 23 ± 2 kg/m2, x̅ ± SD). Participants arrived fasted overnight and were fed a high carbohydrate meal (90 g glucose), raising BGL from fasting baseline (4.4 ± 0.3 mmol/L) to peak BGL (8.5 ± 0.3 mmol/L) 45 min after the meal. Participants consumed the supplement 45 min after the meal, and both caffeine and C. annuum fruit powder restored BGL (F (8,178) = 2.2, p = 0.02) to near fasting levels within 15 min of supplementation compared to placebo (120 min). In parallel both supplements increased energy expenditure (F (2, 21) = 175.6, p < 0.001) over the 120-min test period (caffeine = 50.74 ± 2 kcal/kg/min, C. annuum fruit = 50.95 ± 1 kcal/kg/min, placebo = 29.34 ± 1 kcal/kg/min). Both caffeine and C. annuum fruit powder increased supraclavicular fossa temperature (F (2,42) = 32, p < 0.001) on both day 1 and day 7 of testing over the 120-min test period. No statistical difference in core temperature or reference point temperature, mean arterial pressure or heart rate was observed due to supplementation nor was any statistical difference seen between day 1 and day 7 of intervention. This is important for implementing dietary ingredients as potential metabolism increasing supplements. Together the results imply that through dietary supplements such as caffeine and C. annuum, mechanisms for increasing metabolism can be potentially targeted to improve metabolic homeostasis in people.